Particle shape characterizations for energetic materials by computational geometry and stereology method - Xianzhen Jia; Ruipeng Liu; Haichao Ren; Yutong Han; Jian Ouyang; Hang Zheng; Cao Peng; Junxing Zheng (SN Applied Sciences, 2022)
Article highlights 1. The 3D particle geometries of typical energetic materials are scanned by X-ray CT and identified by improved watershed analysis. 2. The 2D and 3D computational geometry techniques are developed for determining seven commonly used particle shape descriptors. 3. The stereology strategy is used to obtain 2D projections of 3D particles and evaluate the effectiveness of 2D shape descriptors to infer 3D particle shapes of energetic materials.